Student Reflection Papers on a Global Clinical Experience: A Qualitative Study - Carmi Z. Margolis; Robert M. Rohrbaugh; Luisa Tsang; Jennifer Fleischer; Mark J. Graham; Anne Kellett; Janet P. Hafler (Ubiquity Press, 2017)
Background: Many of the 70,000 graduating US medical students [per year] have reported participating in a global health activity at some stage of medical school. This case study design provided a method for understanding the student's experience that included student's learning about culture, health disparities, exposure and reaction to a range of diseases actually encountered. The broad diversity of themes among students indicated that the GCE provided a flexible, personalized experience. We need to understand the student's experience in order to help design appropriate curricular experiences [and valid student assessment]. Objective: Our research aim was to analyze medical student reflection papers to understand how they viewed their Global Clinical Experience (GCE). Methods: A qualitative case study design was used to analyze student reflection papers. All 28 students who participated in a GCE from 2008-2010 and in 2014-2015 and submitted a reflection paper on completion of the GCE were eligible to participate in the study. One student did not submit a reflection paper and was not included in the study. Findings: All 27 papers were coded by paragraph for reflection and for themes. System of Care/Range of Care was mentioned most often, Aids to Adjustment Process was mentioned least. The theme, "Diseases," referred to any mention of a disease in the reflection papers, and 44 diseases were mentioned in the papers. The analysis for depth of reflection yielded the following data: Observation, 81/248 paragraphs; Observation and Interpretation, 130/248 paragraphs; and Observation, Interpretation, and Suggestions for change, 36/248 paragraphs; 9 reflection papers contained 27 separate accounts of a transformational experience. Conclusions: This study provided a method for understanding the student's experience that included student's learning about culture, health disparities, and exposure and reaction to a range of diseases actually encountered. The broad diversity of themes among students indicated that the GCE provided a flexible, personalized experience. How we might design a curriculum to facilitate transformational learning experiences needs further research.